A Probably Minor Role for Land-Applied Goat Manure in the Transmission of Coxiella burnetii to Humans in the 2007–2010 Dutch Q Fever Outbreak - van den Brom, René (PLoS One, 2015)
In 2007, Q fever started to become a major public health problem in the Netherlands, with small ruminants as most probable source. In order to reduce environmental contamination, control measures for manure were implemented because of the assumption that manure was highly contaminated with Coxiella burnetii. The aims of this study were 1) to clarify the role of C. burnetii contaminated manure from dairy goat farms in the transmission of C. burnetii to humans, 2) to assess the impact of manure storage on temperature profiles in dunghills, and 3) to calculate the decimal reduction time of the Nine Mile RSA 493 reference strain of C. burnetii under experimental conditions in different matrices. For these purposes, records on distribution of manure from case and control herds were mapped and a potential relation to incidences of human Q fever was investigated. Additionally, temperatures in two dunghills were measured and related to heat resistance of C. burnetii. Results of negative binomial regression showed no significant association between the incidence of human Q fever cases and the source of manure. Temperature measurements in the core and shell of dunghills on two farms were above 40°C for at least ten consecutive days which would result in a strong reduction of C. burnetii over time. Our findings indicate that there is no relationship between incidence of human Q fever and land applied manure from dairy goat farms with an abortion wave caused by C. burnetii. Temperature measurements in dunghills on two farms with C. burnetii shedding dairy goat herds further support the very limited role of goat manure as a transmission route during the Dutch human Q fever outbreak. It is very likely that the composting process within a dunghill will result in a clear reduction in the number of viable C. burnetii.